Authorial stance in medical research articles and medical case reports written in english by native and non-native authors - Abdulhussein Swear, Muna (2016)
Authorial stance, or stance-taking, in written texts expresses the interpersonal meaning of language, where authors position themselves with regard to the message being written about as well as to the readers. It has also been defined as how the author projects his or her own voice and engages with other voices brought into the text.Authorial stance has been identified as an important skill in effective writing, not only in clearly argumentative texts often associated with the arts and social sciences, but is equally important in scientific writing making for “objective” claims. Two issues provide the basis for this study. First, while authorial stance has been studied widely in a variety of texts, including scientific research texts, little is known about how authorial stance is manifested in medical genres as medical research articles and medical case reports, which are the two most published written genres in the discipline. Second, within the area of medical research writing, the patterns of authorial stance may be influenced by genre in which the writing is done, as well as by the author’s familiarity with the language represented by the author’s native or nonnative speaker status. This thesis examined the patterns of authorial stance in two genres of written medical discourse, medical research articles and medical case reports published in three medical journals within the branch of “Family Medicine.” The texts in English were authored by two groups of medical researchers, native and non-native speakers of English, with Malaysian medical researchers as the non-native group selected for the study. The analysis sought to describe how medical researchers negotiate dialogically with other voices in the texts, argue for specific positions as well as highlight and critique others’ work in the course of advancing their claims. The study adopted the discourse semantic framework of Appraisal (Martin & White, 2005), particularly the Engagement and Graduation subsystems, to identify and describe the stance patterns used by authors in the two genres analysed. Apart from a qualitative analysis of a small portion of the data, a quantitative orientation to the analysis was also adopted utilizing corpus-based methodology in comparing authorial stance patterns found across the individual rhetorical sections of the texts, across genres, and across the native and non-native groups. The overall findings suggest that native speaker authors use relatively more contractive stance in their writing than nonnative speaker authors in their writing. However, the two groups of authors demonstrated different preferences in their use of stance resources in the medical research articles and medical case reports, indicating that genre plays an important role in the author’s interpretation of what and how stance strategies should be deployed to successfully meet the communication purposes and rationale of the genre.